Comparison of forming processes for micro textured cups - Reck, Manuel; Merklein, Marion (51st SME North American Manufacturing Research Conference, 2023)

Comparison of forming processes for micro textured cups - Reck, Manuel; Merklein, Marion (Manufacturing Letters, 2023)
Friction losses are present in all kinds of technical systems. This is always associated with additional energy consumption, which can be partly avoided as it arises. Energy savings can be achieved by a wide range of approaches. The application of friction reducing coatings on bodies in relative motion is widespread. The coating of parts is however only suitable to a limited extent for the production in large batches. Therefore, research approaches consider alternative methods to achieve friction reductions. A promising approach is the integration of miniaturized pockets on the surface of the component. In lubricated contacts, the lubricant can then accumulate in these indentations. The relative motion between two bodies thus builds up a hydrodynamic pressure and consequently reduces friction. Forming technology is suitable for the efficient production of metallic components in large quantities. The aim of this study is therefore to identify challenges in the integration of micro coining in established forming processes. Two processes from sheet metal forming and bulk metal forming are investigated. In a combined experimental and numerical approach, process-specific challenges are derived regarding the texturing process and the numerical process modelling for combined micro coining. The analysis is carried out on a cup geometry, as used in the automotive sector as tappets in the valve train. The case hardening steel 16MnCr5 (1.7131) is used as workpiece material.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Extrusion; Modelling; Sheet metal; Texture

Forming of complex functional elements on sheet metal - Reck, Manuel; Rohrmoser, Andreas; Jobst, Andreas; Pilz, Florian; Merklein, Marion (Sheet Bulk Metal Forming, 2021)

Forming of lightweight helical gears by means of sheet-bulk metal forming - Reck, Manuel; Merklein, Marion (2024)

Grundlegendes Prozessverständnis zur Herstellung von Bauteilen mit texturierten Oberflächen durch Mikroprägen in einem kombinierten Umformprozess - Reck, Manuel (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2025)
Durch die steigende Nachfrage nach Bauteilen mit hoher Funktionsdichte gewinnen metallische Komponenten mit texturierter Oberfläche an Bedeutung. Texturierte Oberflächen sind häufig aus der Natur inspiriert und können verschiedene Funktionen wie eine reduzierte Reibung oder eine angepasste Benetzbarkeit bereitstellen. Konventionelle Herstellungsverfahren solcher Bauteile geraten durch lange Prozesszeiten und hohe Fertigungskosten bisweilen an ihre Grenzen. Im Rahmen dieser Arbeit wird daher ein kombiniertes Umformverfahren untersucht, das die Herstellung von Bauteilgrundkörpern mit der Texturierung der Oberfläche in einem ressourceneffizienten Prozess verbindet. Die Zielsetzung der Arbeit ist die Erarbeitung eines grundlegenden Prozessverständnisses der umformtechnischen Fertigung dünnwandiger Komponenten mit mikrogeprägten Strukturen in einem einstufigen Verfahren. Die Prozessanalyse erfolgt anhand der Untersuchung von bauteil- und prozessspezifischen Herausforderungen sowie der anschließenden Ableitung von Grenzen der Formgebung. Eine systematische Einflussanalyse zudem Aufschluss über die Wirkmechanismen der Prozesskombination. Darauf basierend werden Methoden zur Erweiterung der Prozessgrenzen erarbeitet und bereitgestellt. Im Hinblick auf den industriellen Einsatz wird das werkzeugseitige Verschleißverhalten in der Fertigung großer Stückzahlen untersucht. Aus den erzielten Erkenntnissen werden anwendungsnahe Empfehlungen für kombinierte Texturierungsprozesse abgeleite

Investigation on micro textured tappets from design and production to the application properties - Reck, Manuel; Orgeldinger, Christian; Tremmel, Stephan; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers Part L-Journal of Materials-Design and Applications, 2022)

Investigation on tailored blanks in a full forward extrusion process of sheet-bulk metal forming - Reck, Manuel; Merklein, Marion (ESAFORM 2021, 2021)

Investigation on tool properties for the production of components with micro textured surfaces - Reck, Manuel; Merklein, Marion (IOP Conference Series: Materials Science and Engineering, 2022)

Process-Integrated Component Microtexturing for Tribologically Optimized Contacts Using the Example of the Cam Tappet—Numerical Design, Manufacturing, DLC-Coating and Experimental Analysis - Orgeldinger, Christian; Reck, Manuel; Seynstahl, Armin; Rosnitschek, Tobias; Merklein, Marion; Tremmel, Stephan (Lubricants, 2024)

Wear Analysis of Micro Textured Coining Tools - Reck, Manuel; Merklein, Marion (XLI. Colloquium on Metal Forming, 2023)